2020
DOI: 10.4103/ams.ams_40_20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sticky bone as a novel autologous graft for mandibular third molar extraction socket healing - An evaluative study

Abstract: Introduction: Recently, initiation and enhancement of extraction socket healing has been amplified by platelet concentrates, whereas the positive role of Sticky bone has been focused on maintaining alveolar bone dimensions. This study aimed to determine the effectiveness of Sticky Bone for socket grafting of mandibular third molars (M3Ms) in terms of soft- and hard-tissue healing. Materials and Methods: This split-mouth prospective trial constituted prophylactic removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…However, our study results showed no significant difference in VAS scores on the 3rd and 7th postoperative days between the case and control groups. Similar results were found in another study which included 75 patients and they concluded that A-PRF has no positive effect on postoperative sequelae [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, our study results showed no significant difference in VAS scores on the 3rd and 7th postoperative days between the case and control groups. Similar results were found in another study which included 75 patients and they concluded that A-PRF has no positive effect on postoperative sequelae [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…There are many different ARP techniques and various types of materials, such as autogenous bone [ 5 ], allografts [ 6 ], xenografts and platelet concentrates [ 7 , 8 ]. The main goal of the bone graft material is to serve as a scaffold and maintain a space for bone ingrowth, blood vessels formation, to support soft tissues and to improve the quality and quantity of regenerated bone [ 9 ]. DBBM is a classical xenogeneic bone graft material, which is made from deorganized bovine limb bone, and generally biocompatible and structurally similar to human bone.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020 Rupawala et al 16 investigated the bone regeneration capacity of sticky bone graft placed in extraction socket of lower wisdom tooth. In a split mouth study on 47 patients, the study compared the pain, swelling and stated a rapid bone healing with better bone density after 3 months.…”
Section: Discussionmentioning
confidence: 99%